2020
DOI: 10.1109/access.2020.2986513
|View full text |Cite
|
Sign up to set email alerts
|

Single Crossbar Array of Memristors With Bipolar Inputs for Neuromorphic Image Recognition

Abstract: In this paper, we propose a new crossbar architecture of memristors with bipolar inputs for an image recognition application. The performance of the proposed crossbar array with bipolar inputs is based on the simplified Exclusive-NOR function to measure the similarity between the input pattern and the stored patterns. In the proposed architecture, only one crossbar array is used instead of two crossbar arrays. The number of memristors in the proposed architecture is reduced by 50%, when compared to the complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The k th output, I k , contained the amount of the similarity between the input vector A and the k th stored pattern. The winner-takes-all circuit was used to finally choose the maximum I k , which showed that the input vector A matched the k th prestored pattern, i.e., k th prestored image [14][15][16].…”
Section: Simulations and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The k th output, I k , contained the amount of the similarity between the input vector A and the k th stored pattern. The winner-takes-all circuit was used to finally choose the maximum I k , which showed that the input vector A matched the k th prestored pattern, i.e., k th prestored image [14][15][16].…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…By simplifying the XNOR in Equation ( 4), a new single memristor crossbar array has been shown to be capable of measuring the similarity between two vectors for the application of image recognition [16]. The XNOR function in Equation ( 4) is simplified as Equation ( 6) [16]:…”
Section: The Single Memristor Crossbar Arraymentioning
confidence: 99%
See 3 more Smart Citations